Gastric trichobezoar and Rapunzel syndrome - Mendoza-Sayán, Angel (2020)
A 17-year-old teenager, with poor social conditions, was admitted for persistent abdominal pain that worsened in the last two weeks, with nausea, vomiting, abdominal distention and weight loss. On stand position abdomen x-ray, ultrasound and abdominal CT showed an upper intestinal occlusion for which she was urgently operated. Exploratory laparotomy with anterior gastrostomy showed a bezoar-compatible mass, extending from the gastric fundus to the second portion of duodenum causing intestinal subocclusion. The postoperative evolution was favorable and she was discharged with follow-up by general surgery and psychiatry.